Functional regulation of p73 and p63: development and cancer. - Melino, G; Lu, X; Gasco, M; Crook, T; Knight, R (2003)
The transcription factor and tumour suppressor p53 and its two homologues p63 and p73 form a family of proteins. p63 and p73 show much greater molecular complexity than p53 because they are expressed both as multiple alternatively spliced C-terminal isoforms, and as N-terminally deleted, dominant-negative proteins that show reciprocal functional regulation. In addition, several other factors, such as post-translational modifications and specific and common family regulatory proteins, result overall in subtle modulation of their biological effects. Although all p53, p63 and p73 family members are regulators of the cell cycle and apoptosis, the developmental abnormalities of p73- and p63-null mice do not show enhanced tumour susceptibility of p53 knockouts, suggesting that complex regulatory processes modulate the functional effects of this family of proteins.